FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KESELAMATAN BERKENDARA PADA PENGEMUDI OJEK ONLINE DI KOMUNITAS SAHABAT G2 INDEPENDENT TAHUN 2023 - Anggita Megawati, (2023)
Safety riding behavior is an important aspect for online motorcyclists. Members of Sahabat G2 Independent community have experienced traffic accidents that have resulted in injuries, comas, and even deaths. The study aims to analyze the factors that influence safety riding behavior among online motorcyclists in the Sahabat G2 Independent Community in 2023. The study is a quantitative study with a cross-sectional study design. The study population was online motorcycle drivers in the Sahabat G2 Independent Community, with a sample size of 75 people taken using the total population sampling technique. The results show that 48% of drivers show unsafe behavior while riding. There is a significant relationship between knowledge (p- value = 0,015), attitude (p-value = 0,004), perception (p-value = 0,002), hydration status (p-value = 0,004), and the role of co-workers (p-value = 0,002) with safety riding behavior. However, there is no significant relationship between age, duration of work, riding safety training, and working period with safety riding behavior. The study concluded that there was an influence of knowledge, attitude, perception, hydration status, and the role of co-workers on safety riding behavior. Drivers are expected to be able to wear self-protection equipment such as gloves and shoes while driving.